Jurisprudential analysis of the mafia game; Emphasizing the elements of lies, deception and the nature of play - mohamad hasanzadeh (پژوهش‌های فقهی مسائل مستحدثه)
Mafia game; Emerging and pervasive entertainment among Muslim youth. Since in this game, the approach of the mafia members is to lie and deceive the citizens of the game, the jurisprudential evidence of banning falsehood (lying as a joke) has attracted attention. Also, the alleged evidence of the absolute ban of any type of game also declares its affiliation with the mafia. Now, it should be noted that according to the analysis of the inferential evidence, the completeness of the evidence sanctioning falsehood (lying as a joke) causes the banning of the mafia game, although the implication of the evidence of the absolute banning of the game and ultimately the banning of the mafia game is not complete, and for this reason it is violated O jurist, it does not enter into it. The upcoming research does not have an effective or ineffective background, which shows the emerging effects and dynamics of Jafari's jurisprudence. This jurisprudential research is organized with descriptive analytical method and library information and it is hoped that it will be effective.